The Berenstain Bears go to school - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1978)
Sister Bear, nervous about entering kindergarten, overcomes her fears when she discovers that school is really fun.
Booklist.
3.0
K-3
Keywords: Bears -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; Schools -- Fiction; Bears -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; School stories